Ki-67 Proliferative Activity in the Tumor Margins as a Robust Prognosis Factor in Glioblastoma Patients - Tejada, Sonia; Becerra-Castro, Maria Victoria; Nuñez-Cordoba, Jorge; Díez-Valle, Ricardo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Introduction The infiltrative margin of glioblastomas (GBM) contains proliferative tumor cells difficult to estimate radiologically as they are included in the hyperintense signal of T2 sequences and they remain in the cavity margin after tumor resection. The amount of these cells could determine overall survival (OS) of these patients.Material and Methods From October 2007 to January 2010, patients whose MRI were suggestive of newly diagnosed, resectable high-grade glioma were operated using fluorescence-guided surgery (FGS). Separate samples were selectively taken from nonfluorescent white matter areas just adjacent to the border of the pale fluorescence and staining was made for Ki-67. OS was analyzed with Kaplan–Meier and Cox regression. Multivariate analysis included the following prognosis variables: age, extent of resection (EOR), O-6-methylguanine-DNA methyltransferase (MGMT) promoter methylation, and performance status index.Results Sample included 65 patients, comprising 37 men and 28 women, with a median Karnofsky Performance Score (KPS) of 80 (40–100) and mean age of 60 (34–78) years. Mean preoperative tumor volume was 35.8 mL. EOR was 100% in 52 patients (80%), with the lower EOR being 88%. For Ki-67, 39 patients had <5% and 26 had ≥5%. OS was 26.8 months (95% confidence interval [CI]: 18.9–28.2) for the Ki-67 low group versus 15.8 months (95% CI: 7.7–18.2) for the Ki-67 high group (p = 0.002).Conclusion Proliferative activity in the normal-looking brain around the resection cavity measured with Ki-67 immunostaining is an important independent prognostic factor for GBM cases with complete resection of enhancing tumor. When complete resection is not reached, this factor is not relevant for prognosis.
Keywords: proliferative invasive tumor; Ki-67 prognosis factor; Glioma extent of resection